Length of weaning period but not timing of vaccination affects feedlot finishing performance and carcass characteristics of fall-weaned, ranch-direct beef calves - Macek, M.J.; Iliff, J.W.; Schmidt, Todd W.; Pacheco, L.A.; Olson, K. C.; Jaeger, John R.; Thomson, Daniel U. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Bovine respiratory disease decreases profitability associated with cattle feeding. The cost of respiratory disease includes death loss, expenses associated with treatment, and reduced growth performance. Respiratory disease also decreases carcass weights, USDA quality grade, and ribeye area of feedlot cattle. Decreased carcass weights, fat thickness, and ribeye area have been associated with treatment of apparent respiratory disease when compared to animals not treated, whereas reduced incidence of the disease resulted in improved carcass merit. Preshipment weaning and vaccination has been found not only to prepare calves for improved performance in feedlots, but also to reduce incidence and severity of respiratory disease. Previous KSU research reported that length of the preshipment weaning period influenced carcass characteristics and time on feed during finishing. Therefore, we hypothesized that vaccination strategy and the length of the preshipment weaning period would interact to influence calf performance during finishing as well as subsequent carcass characteristics. The objective of our experiment was to compare the effects of respiratory disease vaccination administered prior to weaning on the ranch of origin or after feedlot arrival for calves weaned 45, 15, or 0 days before feedlot arrival.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Weaning; Feedlot; Performance; Carcass characteristics